Paper valentine - Yovanoff, Brenna (New York : Razorbill, 2013)
Followed everywhere by the ghost of her recently deceased best friend, Hannah investigates the serial murders of young girls in her community.
Keywords: Grief -- Juvenile fiction; Ghost stories; Serial murderers -- Juvenile fiction; Grief -- Fiction; Ghosts -- Fiction; Serial murderers -- Fiction; Ghost stories